A duplex fluorescent quantitative PCR assay to distinguish the genotype I, II and I/II recombinant strains of African swine fever virus in China - Hu, Zhiqiang; Lai, Ranran; Tian, Xiaogang; Guan, Ran; Li, Xiaowen (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) is a severe, hemorrhagic, and highly contagious disease caused by the African swine fever virus (ASFV) in both domestic pigs and wild boars. In China, ASFV has been present for over six years, with three genotypes of strains prevalent in field conditions: genotype I, genotype II, and genotype I/II recombinant strains. In order to differentiate among these three ASFV genotypes, a duplex fluorescent quantitative PCR method was established using specific probes and primers designed based on viral genes MGF_110-1L and O61R from ASFV strains reported in the GenBank database. Following optimization of reaction conditions, a duplex fluorescent quantitative PCR method was successfully developed. This method demonstrated no cross-reactivity with porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), porcine reproductive and respiratory syndrome virus (PRRSV), classic swine fever virus (CSFV), porcine pseudorabies virus (PRV), porcine circovirus 2 (PCV2), porcine circovirus 3 (PCV3), highlighting its specificity. Sensitivity analysis revealed that the limits of detection (LODs) of this method were 2.95 × 10−1 copies/μL for the MGF_110-1L gene and 2.95 × 100 copies/μL for the O61R gene. The inter- and intra-group coefficients of variation were both <1%, indicating high reproducibility. In summary, the establishment of this duplex fluorescent quantitative PCR method not only addresses the identification of the ASFV recombinant strains but also allows for simultaneous identification of the three epidemic genotype strains.